Menangkal Radikalisme Agama Menguatkan Perdamaian Umat di Toraja Melalui Penggunaan Kitab Keagamaan dan Nilai Budaya Orang Toraja - Theofilus Welem (Purwadita : Jurnal Agama dan Budaya, 2023)
Writing This background about anxiety will problem religious radicalism that brings split for public lately this. Although during This Not yet sound action radicalism on deep religious basis life people religion in Toraja will but threat from beyond what can just bring up matter the need for watch out. Writing This aim for describe use book religion (Bible and the Koran) and mark culture toraja as bridge in ward off radicalism and strengthening peace people religion in Toraja. Method research to be used is method qualitative with approach descriptive. Results found is Book religious containing text about life each other love neither word nor action and text the can combined together with mark culture Toraja that lasts This lived by public Toraja because values culture the can Also found in texts book religious. Conclusion from writing This is that book religion and mark culture Toraja can used as bridge in ward off action radicalism and guard peace people in Toraja Because text theological and non-theological the own role important in life society as people religious at a time cultured society Because owned values inside it can combine for strengthen life harmony in society.